PENGARUH SIKAP INDIVIDU, NORMA SUBJEKTIF, DAN PERSEPSI KONTROL PERILAKU TERHADAP NIAT BEPERGIAN - Ricky Husada Saputra; Olivia Barcelona Nasution (Universitas Ahmad Dahlan, 2022)
This study aims to determine the effect of individual attitude, subjective norm, and perception of behavioral control on travel intentions during the Covid-19 pandemic. Respondents in this study were students in the Special Region of Yogyakarta who wanted to travel during the Covid-19 pandemic. Data collection techniques were carried out using questionnaires distributed through google forms and 205 respondents were obtained. The results of the study prove that individual attitude have a positive but no significant effect on travel intentions during the Covid-19 pandemic. Then, the subjective norm have a positive effect on travel intentions during the Covid-19 pandemic. Last, perception of behavioral control have a positive effect on travel intentions during the Covid-19 pandemicThis study aims to determine the effect of individual attitude, subjective norm, and perception of behavioral control on travel intentions during the Covid-19 pandemic. Respondents in this study were students in the Special Region of Yogyakarta who wanted to travel during the Covid-19 pandemic. Data collection techniques were carried out using questionnaires distributed through google forms and 205 respondents were obtained. The results of the study prove that individual attitude have a positive but no significant effect on travel intentions during the Covid-19 pandemic. Then, the subjective norm have a positive effect on travel intentions during the Covid-19 pandemic. Last, perception of behavioral control have a positive effect on travel intentions during the Covid-19 pandemic.